2018
DOI: 10.1016/j.cell.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Western Diet Triggers NLRP3-Dependent Innate Immune Reprogramming

Abstract: Long-term epigenetic reprogramming of innate immune cells in response to microbes, also termed "trained immunity," causes prolonged altered cellular functionality to protect from secondary infections. Here, we investigated whether sterile triggers of inflammation induce trained immunity and thereby influence innate immune responses. Western diet (WD) feeding of Ldlr mice induced systemic inflammation, which was undetectable in serum soon after mice were shifted back to a chow diet (CD). In contrast, myeloid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
777
1
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 757 publications
(825 citation statements)
references
References 39 publications
(54 reference statements)
38
777
1
9
Order By: Relevance
“…The significantly higher expression of NLRP3, ASC, and caspase‐1 in SBS rats suggests NLRP3 inflammasome activation in SBS. Recent studies indicate that NLRP3 might be regulated by dietary factors, which could be used as potential nutrition interventions in different diseases . Ng et al found that the activation of the NLRP3 inflammasome pathway was inhibited by MUC1, which is a component of MFGM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significantly higher expression of NLRP3, ASC, and caspase‐1 in SBS rats suggests NLRP3 inflammasome activation in SBS. Recent studies indicate that NLRP3 might be regulated by dietary factors, which could be used as potential nutrition interventions in different diseases . Ng et al found that the activation of the NLRP3 inflammasome pathway was inhibited by MUC1, which is a component of MFGM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that NLRP3 might be regulated by dietary factors, which could be used as potential nutrition interventions in different diseases. 36,37 Ng et al found that the activation of the NLRP3 inflammasome pathway was inhibited by MUC1, 16 which is a component of MFGM. In this study, higher expression of MUC1 with suppression of NLRP3 pathway in ileum was observed in the SBS+MFGM group.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, mice fed even transiently (4 weeks) with a western diet displayed HSC proliferation, skewing of HSC lineages and exaggerated responses to a variety of inflammatory assaults. HSC chromatin accessibility was altered in a manner that was traced to the inflammasome activator NLRP3 (NLR Family Pyrin Domain Containing 3 NLR Family Pyrin Domain Containing 3), which in response to a “Western” diet metabolite, became activated to process and release the pro-inflammatory cytokine IL-1β (Christ et al, 2018). Exactly how IL1β sets off its downstream effectors to elicit sustained changes in chromatin accessibility remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…b-glucan and other stimuli including the BCG vaccine and Western diets trigger reprogramming of haematopoietic stem cells within the bone marrow that give rise to circulating trained monocytes, explaining some aspects of the long-lasting effect of trained immunity [70,71]. b-glucan and other stimuli including the BCG vaccine and Western diets trigger reprogramming of haematopoietic stem cells within the bone marrow that give rise to circulating trained monocytes, explaining some aspects of the long-lasting effect of trained immunity [70,71].…”
Section: Metabolic Aspects Of Trained Immunitymentioning
confidence: 99%